Oncology and infertility: selected issues. Part I. What causes fertility disorders? - Mazur-Roszak, Małgorzata; Tomczak, Piotr; Litwiniuk, Maria; Markowska, Janina (Contemporary Oncology/Współczesna Onkologia, 2005)
The surveillance data indicate that the number of young patients with neoplastic diseases is gradually increasing. Many of those patients are concerned about the impact of their disease and the proposed therapy on their fertility. Practically, each type of cancer therapy including surgery, radiation treatment, chemotherapy or hormonal treatments, can affect the gonadal function. Surgery, the oldest proven treatment of cancer, consists in the removal of the affected organ. The surgical treatment of genitourinary cancers may have a direct effect on fertility. Sometimes, due to metastasis, the gonads are also removed. Finally, pelvic surgery (in patients with bladder, rectal, prostate, or testicular cancer) may damage the nerves, thus resulting in impotence. The radiation therapy may affect fertility when the gonads are situated in the irradiation field. The degree of the damage to the function of the gonads depends on the location of the irradiation fields, the total dose and the patient’s age. Chemotherapy is an effective treatment method of testicular cancer, Hodgkin’s disease, some lymphomas and leukemias. It is also part of therapy used in many other cancers (for example breast cancer). The fertility disorders after chemotherapy concern both males and females, although there is a greater risk for the man to suffer from permanent sterility. The impact of chemotherapy on the gonads is a function of the type of the chemotherapy administered, the cumulative dose, and the age of the patient. Alkylating agents, notably cyclophosphamide, are most clearly associated with the gonadal dysfunction. Younger women are less likely to develop permanent amenorrhea after chemotherapy. It should be emphasized, however, that the fertility of patients with cancer can be depleted because of the disease itself. infertility, oncology, chemotherapy, radiotherapy, surgery.